TEACHER’S PERCEPTION TOWARD THE USE OF DIALOGUE IN IMPROVING ENGLISH COMMUNICATION AT PGRI SENIOR HIGH SCHOOL OF PAGARALAM - Ferly Herlizon (SMART: Journal of Multidisciplinary Educational, 2023)
This research is intended to know and analyze the teacher’s perception toward the use of dialogue in improving English communication at PGRI senior high school of Pagaralam. This research is descriptive qualitative research. Observations, interviews, questionnaires, and documents were used to collect data in this research. Sources of data used by researchers are interviews and questionaires used talks with teachers. because of that researchers get accurate information about what was done during the activity and find out the results of these activities using the data types and data sources described. The results of this research indicate that conversational learning using dialogue could improve communication, and students' motivation to learn English.   Keywords: Perception, Dialogue, English Communication